Composite collector, flotation agent and method for low-grade lithium ore
By developing a composite collector containing saponified industrial oleic acid, kerosene, alcohol and specific compounds, the problem of unsatisfactory flotation selectivity and recovery rate of low-grade composite lithium ore was solved, and efficient lithium ore flotation recovery was achieved, achieving a recovery rate of more than 70%.
Patent Information
- Application Number
- CN202211135945.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-19
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-09-19
AI Technical Summary
When handling low-grade composite lithium ore, the selectivity and recovery rate are not ideal, making it difficult to achieve efficient flotation recovery.
A composite collector containing saponified industrial oleic acid, kerosene, alcohol and specific compounds was developed to improve the flotation performance of lithium ores through synergistic effects, especially in low-grade polyphase lithium ores.
It has achieved efficient flotation recovery of ultra-low-grade styrofoamline, lithium mica and phosphate lithium aluminite composite lithium ore, and the Li2O recovery rate has reached 71.64%, meeting the lithium ore development standards.
Smart Images

Figure CN115582223B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of mineral processing, and in particular relates to the flotation field of ultra-low-grade complex lithium ore. Background Art
[0002] Lithium metal and lithium compounds have excellent physical and chemical properties and are widely used in high-energy batteries, aerospace, ceramic industry, food storage, medicine and agriculture. With the rapid development of high-tech at home and abroad and the surging demand for lithium in the new energy industry, the efficient development and utilization of lithium mineral resources is also imminent.
[0003] Domestic solid ore lithium resources are mainly distributed in Sichuan, Hunan, Xinjiang, Guizhou, Jiangxi and Henan. Except for the granite pegmatite lithium mine in Henan, which has not been put into production, large lithium mines in other regions have been built or are planned to be put into production. This is mainly because the lithium-containing minerals in Henan are diverse, not a single lithium-containing mineral. The main lithium-containing minerals are spodumene (theoretical Li2O content is only 6.06%), lepidolite (theoretical Li2O content is 3.0% to 7.75%), and pyroxenite (theoretical Li2O content is 9.29%). The average grade of Li2O in this mining area is only 0.73% (the distribution rates of spodumene, lepidolite and phosphatic lithium aluminum stone are 46.57%, 43.84% and 9.59% respectively), which is an ultra-low-grade composite lithium ore. Due to the large differences in the properties of different lithium-containing minerals and the low grade of Li2O, the associated gangue minerals are mainly feldspar, quartz, muscovite and other minerals, most of which are easy to mud. The separation effect of existing mineral processing technology is not good. These problems make the mineral processing recovery rate of this type of lithium ore unable to exceed 70%, thus failing to meet the requirements of plant construction and production. In addition, lithium-containing mines at home and abroad are gradually tending to low grade and lithium ore diversity. Therefore, the development of efficient separation technology for processing low-grade composite lithium ores has become a problem to be solved.
[0004] According to the above problems, the development of composite collectors with high selectivity and strong collection capacity and new sorting technology has become the key to the recycling of this type of lithium ore. The conventional spodumene ore process is first stirred with strong alkali, then activated with calcium chloride, and finally flotation recovery by adding oxidized paraffin soap and cyclopentane acid soap. The application effect of composite lithium ore is not good. On the one hand, calcium chloride can only activate spodumene, but cannot activate spodumene, lepidolite and pyroxenite well. On the other hand, the collector has poor selectivity and weak collection capacity, which cannot achieve efficient flotation recovery of composite lithium ore. Summary of the invention
[0005] In view of the problem that the existing collectors have unsatisfactory collection performance for low-grade composite lithium ores, the first purpose of the present invention is to provide a lithium ore composite collector, aiming to provide a composite collector with excellent collection ability for lithium ores, especially low-grade composite lithium ores.
[0006] The second object of the present invention is to provide the flotation application of the composite collector in lithium ore, especially in low-grade composite lithium ore.
[0007] The third object of the present invention is to provide a flotation reagent comprising the composite collector.
[0008] The fourth object of the present invention is to provide a method for flotation separation of lithium ore, especially low-grade lithium ore, aiming to achieve effective flotation of lithium ore based on the composite collector and flotation agent.
[0009] The more diverse the lithium ore types are, the lower the Li2O content is, and the more difficult the flotation recovery is. In addition, there are differences in the properties of different lithium ore types such as spodumene, lepidolite and pyroxenite, making it difficult to achieve joint synchronous flotation based on a set of flotation methods. In view of the problems that the existing lithium ore flotation methods have unsatisfactory selectivity, recovery rate and grade for the joint flotation of low-grade composite lithium ore, the present invention provides the following technical solutions:
[0010] A lithium ore composite collector, comprising saponified industrial oleic acid, kerosene, C4-C9 alcohol and a compound of formula 1;
[0011]
[0012] R is C4~C 20 An alkyl group or an alkoxyalkyl group, wherein n is 1 to 14;
[0013] The saponified industrial oleic acid is industrial oleic acid saponified with at least one cation of sodium or potassium, and its saponification rate is 40-100%.
[0014] The present invention has found that the components of the combination can achieve synergy and can effectively improve the flotation performance of lithium ore, especially for low-grade and multi-phase lithium ore, it has excellent joint flotation selectivity of multiple lithium mineral phases, and effectively improves the joint flotation recovery effect of low-grade multi-type lithium ore.
[0015] In the present invention, the combination of saponified industrial oleic acid, kerosene, alcohol and the compound of formula 1 is the key to synergistically improving the selective flotation recovery of lithium ore, especially low-grade multi-phase lithium ore.
[0016] In the present invention, the control of industrial oleic acid and saponification rate helps to cooperate with other components to improve the effective flotation of lithium ore, especially low-grade multi-phase lithium ore.
[0017] Preferably, the industrial oleic acid comprises 55-80 parts by weight of oleic acid, 15-35 parts by weight of linoleic acid, and 5-15 parts by weight of linolenic acid; further, it may comprise 65-75 parts by weight of oleic acid, 18-22 parts by weight of linoleic acid, and 8-12 parts by weight of linolenic acid.
[0018] Preferably, the saponified industrial oleic acid is obtained by saponifying industrial oleic acid and an alkaline component, and the alkaline component is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate.
[0019] In the present invention, the saponification step is, for example, to completely dissolve the alkaline substance in the aqueous solution, control the temperature at 40-60° C., and then slowly add industrial oleic acid to carry out saponification reaction.
[0020] Preferably, the weight ratio of industrial oleic acid to alkaline component is 50-65:5-10;
[0021] Preferably, the saponification rate of the saponified industrial oleic acid is 40 to 80%, more preferably 40 to 60%.
[0022] Preferably, the alcohol is a C6-C8 primary alcohol;
[0023] Preferably, in the compound of formula 1, the R is preferably located in the para position, and preferably, the R is C7 to C 16 wherein n is 5 or 12.
[0024] Preferably, the weight ratio of saponified industrial oleic acid, kerosene, alcohol and the compound of formula 1 is 55-80:10-20:5-15:4-10; more preferably 56-74:14-20:8-14:4-10.
[0025] In the present invention, the preparation method of the composite collector is, for example, as follows: according to the mass ratio, the alkaline substance is completely dissolved in the aqueous solution, the temperature is controlled at 40-60°C, and then industrial oleic acid is slowly added and stirred at a uniform speed in an ultrasonic oscillator for 10-20 minutes. After the solution becomes transparent, alcohol is added, and the stirring is continued at a uniform speed in the ultrasonic oscillator for 5-10 minutes, and then kerosene and formula 1 are added. Finally, the mixed solution is added to the reactor, and the composite collector solution is obtained after being fully stirred at 60-80°C and cooled. It can also be dried to form a solid flotation collector as needed.
[0026] The present invention provides an application of the lithium ore composite collector, which is used for the flotation of lithium ore;
[0027] Preferably, it is used for flotation of low-grade lithium ore;
[0028] Preferably, it is used for the flotation of lithium ores with a Li2O grade of less than or equal to 1%, preferably less than or equal to 0.75%;
[0029] Preferably, it is used for the flotation of at least one lithium ore selected from spodumene, lepidolite and pyroxenite;
[0030] Preferably, it is used for the flotation of two or more composite lithium ores among spodumene, lepidolite and pyroxenite.
[0031] The present invention also provides a lithium ore composite flotation reagent, comprising the lithium ore composite collector and a water-soluble copper salt.
[0032] The present invention has found that the combination of the flotation collector and the water-soluble copper salt can achieve synergy and can unexpectedly significantly improve the effective flotation separation of low-grade multi-phase lithium ore.
[0033] In the present invention, the water-soluble copper salt is at least one of copper sulfate, copper chloride, copper nitrate, copper acetate and copper citrate;
[0034] Preferably, it further comprises a pH adjuster;
[0035] Preferably, the pH adjuster is at least one of sodium carbonate, sodium hydroxide, hydrochloric acid and sulfuric acid.
[0036] Preferably, the flotation reagent may further include ingredients that are theoretically allowed to be added according to flotation requirements.
[0037] Preferably, in the lithium ore composite flotation reagent, each component exists independently of each other before use, or some or all of the components exist in the form of a mixture;
[0038] Preferably, in the lithium ore composite flotation reagent, the weight portion of the lithium ore composite collector is 30 to 50 parts;
[0039] The weight portion of the water-soluble copper salt is 5 to 15 parts;
[0040] The weight portion of the pH adjuster is 45 to 65 parts;
[0041] The present invention also provides a flotation method for lithium ore, wherein the lithium ore is floated using a flotation reagent comprising the composite collector of the present invention.
[0042] Preferably, the lithium ore is floated using the flotation agent described in the present invention.
[0043] In the present invention, the lithium ore is a lithium ore with a Li2O grade of less than or equal to 1%, preferably less than or equal to 0.75%;
[0044] Preferably, the lithium ore is at least one of spodumene, lepidolite and ferromagnetic acid; preferably, it is a composite lithium ore comprising two or more of spodumene, lepidolite and ferromagnetic acid;
[0045] Preferably, the lithium ore is preliminarily subjected to demagnetization and desludging treatments before flotation treatment.
[0046] In the present invention, the flotation step is: the lithium ore and the alkaline substance are subjected to joint grinding, followed by demagnetization and desludging to obtain ore pulp;
[0047] The pH of the ore pulp is regulated, and a water-soluble copper salt and the composite collector are added to perform flotation to obtain lithium concentrate.
[0048] The pH of the pulp during the flotation stage is 10-11;
[0049] The dosage of the composite collector is 600-1500 g / t, preferably 800-1200 g / t;
[0050] The amount of water-soluble copper salt used is 80 to 400 g / t, preferably 100 to 300 g / t.
[0051] In the present invention, the flotation process and operation are carried out by using existing means, for example, the impurity removal open circuit and flotation closed circuit process flow of "one stage of strong magnetic separation to remove magnetic minerals, one stage of strong stirring to remove mud, one lithium roughing selection, one lithium scavenging selection, three lithium concentrating selections, and sequential return of intermediate ore" can be adopted to obtain magnetic minerals, fine mud, lithium concentrate and tailings.
[0052] The present invention provides a preferred flotation method for low-grade composite lithium ore, the steps comprising:
[0053] 1. Grind the -2mm ultra-low-grade composite lithium ore, add 300-600g / t of sodium carbonate and 150-300g / t of sodium hydroxide, add clean water to control the grinding slurry concentration, the grinding fineness is -0.074mm and the content accounts for 55%-65%, and obtain lithium ore slurry;
[0054] 2. The lithium ore pulp is subjected to strong magnetic separation with a magnetic field strength of 1.0 to 1.4 T to remove magnetic minerals and obtain non-magnetic lithium ore pulp; strong magnetic separation is used to remove easily floating magnetic gangue minerals (the easily floating magnetic gangue minerals are garnet, limonite, magnetite, biotite, pyroxene, amphibole, tourmaline, etc.) to prevent magnetic gangue minerals from entering the flotation lithium concentrate and affecting the quality.
[0055] 3. Add the non-magnetic lithium ore slurry into the flotation tank and stir for 5 to 15 minutes, then let it stand for 3 to 9 minutes, remove the fine mud by siphoning, and finally add clean water to make lithium ore flotation slurry;
[0056] 4. Add the lithium ore flotation pulp into a temperature-adjustable flotation machine, control the temperature at 10-40° C., add 800-1800 g / t of sodium carbonate to adjust the pulp pH to 10-11, stir for 2-5 min, do not add inhibitors, then add 50-300 g / t of copper sulfate to the pulp, stir for 2-5 min, then add 400-1000 g / t of the composite lithium ore composite collector, stir for 3-8 min, perform lithium roughing, scrape and foam for 2-6 min, and obtain lithium rough concentrate and lithium rough tailings;
[0057] 5. The lithium rough concentrate is subjected to three concentrations, and 200-600 g / t of sodium carbonate is added each time. The first lithium concentration middlings, the second lithium concentrate middlings and the third lithium concentrate middlings are returned to the previous flotation process in sequence, and the foam scraped from the third concentration is the final lithium concentrate; each concentration in step 5 is supplemented with 200-600 g / t of sodium carbonate, on the one hand, to adjust the pH of the slurry and increase the floatability difference between the lithium ore and the gangue minerals, and on the other hand, to disperse the slurry and promote the shedding of the gangue minerals entrained in the lithium concentrate.
[0058] 6. The lithium rough tailings are scavenged once, 30-100 g / t of copper sulfate is scavenged, stirred for 1-3 min, and then 200-500 g / t of the composite lithium ore composite collector is added, stirred for 2-5 min, lithium scavenging is performed, and the foaming is scraped for 1-4 min. The lithium scavenging concentrate is returned to the lithium roughing in sequence, and the remaining slurry in the tank of the lithium scavenging is the final lithium tailings.
[0059] 7. After flocculation, filtration and drying of the magnetic minerals, fine mud, lithium concentrate and lithium tailings, they are weighed and sampled respectively, and then each sample is put into a three-head agate grinder and ground for 5 to 15 minutes to -0.038 mm, and then taken out for chemical analysis of Li2O grade and calculation of recovery rate.
[0060] The flocculation in step 7 refers to the method of adding flocculants to make the slurry settle quickly, which is more conducive to subsequent filtration operations. Commonly used flocculants are polyaluminum ferric silicate, polyaluminum chloride, polyaluminum sulfate, magnesium sulfate, ferric chloride, polyacrylamide, etc.
[0061] The flocculant is polyaluminium chloride or polyaluminium sulfate. Most preferably, the flocculant is polyaluminium sulfate.
[0062] The "g / t" mentioned in the present invention refers to the number of grams of reagents required to be added to process one ton of raw ore.
[0063] Beneficial Effects
[0064] 1. The present invention provides a composite collector of saponified industrial oleic acid, kerosene, alcohol and a compound of formula 1, which can effectively improve the flotation performance of lithium ore, especially the flotation performance of low-grade multi-phase lithium ore, thanks to the combined synergy of the components. The collector of the present invention realizes the efficient flotation recovery of ultra-low-grade spodumene, lepidolite and pyroxenite composite lithium ore. In addition, the ingredients of the agent of the present invention are widely available, the price is appropriate, non-toxic and harmless, the adaptability is strong, and the low temperature resistance is good, which has application value in actual production.
[0065] 2. The present invention innovatively combines the flotation collector and the water-soluble copper salt, which can achieve further synergy and help to further improve the flotation selectivity of low-grade multi-phase lithium ore.
[0066] 3. In the present invention, the combination of the flotation collector, water-soluble copper salt and pH parameters can further synergistically improve the joint flotation selectivity of low-grade multi-phase lithium ore and improve the joint flotation performance of multi-lithium mineral phases.
[0067] 4. The process of the present invention can realize the effective recovery of low-grade composite phase lithium ore, so that it can obtain higher grade and achieve a recovery rate higher than 70% to meet the plant construction requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 Flotation flow chart used for the examples and comparative examples; DETAILED DESCRIPTION
[0069] The effect of the present invention is illustrated by taking the composite lithium ore of spodumene, lepidolite and phosphatic lithium aluminum stone in a certain area of Sanmenxia, Henan Province as an example. In the following cases, unless otherwise stated, the results of the physical analysis of the raw ore Li2O are shown in Table 1. The main valuable element in the raw ore is lithium, containing 0.73% Li2O. Lithium is mainly found in spodumene, with a distribution rate of 46.57%. It is also found in mica with a large proportion, with a distribution rate of 43.84%. A small amount is found in phosphatic lithium aluminum stone, with a distribution rate of 9.59%. It belongs to the composite lithium ore of ultra-low-grade spodumene, lepidolite and phosphatic lithium aluminum stone.
[0070] Table 1 Phase analysis results of raw Li2O
[0071]
[0072]
[0073] Note: Industrial oleic acid can be commercially available products in the industry. For example, in the following case, the industrial oleic acid component includes 70 parts by weight of oleic acid, 20 parts by weight of linoleic acid, and 10 parts by weight of linolenic acid.
[0074] Example 1
[0075] The process flow and reagent system for separating ultra-low-grade spodumene, lepidolite and pyroxenite composite lithium ore in this embodiment are as follows: Figure 1 As shown, the composite lithium ore in Table 1 was floated with different saponification rates of industrial oleic acid in the composite collector of 40%, 60%, 80% and 100%. The flotation process parameters of each group of cases were the same, and the only difference was the saponification rate of industrial oleic acid, so as to explore the selectivity and flotation effect of the composite collector in this case.
[0076] In this case, the collector is calculated by weight and consists of 68 parts of saponified industrial oleic acid, 12 parts of n-hexanol, 16 parts of kerosene, 4 parts are mixed and after sufficient reaction, a 5% concentration composite collector solution is prepared for standby use.
[0077] The operation process is as follows: the raw ore is first crushed and ball-milled to -0.074mm, accounting for 60%, and then the ore pulp after grinding is subjected to strong magnetic separation, with a magnetic field strength of 1.2T to obtain magnetic minerals; the non-magnetic ore pulp is added to the flotation tank for strong stirring for 10 minutes, and then allowed to stand for 7 minutes, and fine mud and bottom ore pulp are obtained by siphoning; then the bottom ore pulp is supplemented with appropriate clean water in the flotation tank for flotation test; the flotation of ultra-low-grade spodumene, lithium mica and lithium aluminum phosphate composite lithium ore adopts a one-roughing, one-sweeping and three-fine process, and the ore pulp temperature is maintained at 20°C; the first roughing operation: sodium carbonate 1400g / t is added in sequence, the ore pulp pH is 10.5, stirring for 3 minutes, copper sulfate 200g / t, stirring for 3 minutes, composite collector 800g / t, stirring for 5 minutes, flotation for 4 minutes, and lithium roughing concentrate and tailings are obtained. One scavenging operation: add 100g / t of copper sulfate, stir for 2min, 400g / t of composite collector, stir for 3min, float for 3min, and obtain lithium scavenging concentrate and final tailings. Three times of concentration operation: First concentration: add 300g / t of sodium carbonate, stir for 2 minutes, float for 3 minutes, and obtain lithium concentration concentrate and lithium concentration intermediate ore; Second concentration: add 300g / t of sodium carbonate, stir for 2 minutes, float for 3 minutes, and obtain lithium concentration concentrate and lithium concentration intermediate ore; Third concentration: add 300g / t of sodium carbonate, stir for 2 minutes, float for 3 minutes, and obtain final lithium concentrate and lithium concentration intermediate ore; lithium scavenging concentrate and lithium concentration intermediate ore return to the previous operation in sequence.
[0078] Table 2 shows the flotation effect of composite lithium ore at different saponification rates of industrial oleic acid.
[0079] Table 2 Flotation effect of composite lithium ore at different saponification rates of industrial oleic acid
[0080]
[0081] It can be seen from Table 2 that under different saponification rates of industrial oleic acid, the composite collector of the present invention has a good flotation effect on low-grade composite lithium ore; when the saponification rate of industrial oleic acid is equal to 60%, the Li2O grade in the obtainable lithium concentrate is 4.06%, the enrichment ratio is 5.56, and the Li2O recovery rate is 71.64%; when the saponification rate of industrial oleic acid is greater than 60%, the grade and recovery rate of Li2O in the lithium concentrate are only slightly reduced. It shows that the composite collector described in this case 1 can efficiently sort low-grade composite lithium ore within a wide range of saponification rates (between 40 and 100%), and the saponification rate of industrial oleic acid has little effect on its collection ability and has good stability. Comprehensively considering that the saponification rate of industrial oleic acid in the composite collector of the present invention is 60%, it is selected as the preferred one for subsequent experiments and tests.
[0082] Example 2
[0083] In this embodiment, different types of primary alcohols in the composite collector, namely, n-pentanol, n-hexanol, n-heptanol, and n-octanol, are used to flotate the composite lithium ore in Table 1. Figure 1 In the process flow shown, the flotation process parameters of each group of cases are the same, and the only difference is the type of primary alcohol, so as to explore the selectivity and flotation effect of the composite collector in this case.
[0084] In this case, the collector is composed of 68 parts of industrial oleic acid with a saponification rate of 60%, 12 parts of primary alcohol, 16 parts of kerosene, and 4 parts of formula 1-a, calculated by weight. After sufficient reaction, a 5% concentration composite collector solution is prepared for standby use.
[0085] The operation process is consistent with that in Example 1.
[0086] Table 3 shows the flotation effect of composite lithium ore under different types of primary alcohols.
[0087] Table 3 Flotation effect of composite lithium ore under different types of primary alcohol
[0088]
[0089] It can be seen from Table 3 that under different types of primary alcohols, the composite collector of the present invention has a good flotation effect on low-grade composite lithium ore. The Li2O grade in the lithium concentrate that can be obtained is about 4%, the enrichment ratio is greater than 5, and the Li2O recovery rate reaches more than 70%. It shows that the composite collector described in this case 2 can efficiently sort low-grade composite lithium ore under different types of primary alcohols, and different types of primary alcohols have little effect on its collection ability and good stability. Taking into account the comprehensive consideration, the primary alcohol in the composite collector of the present invention is n-octanol, which is selected as the preferred one for subsequent experiments and tests.
[0090] Example 3
[0091] In this embodiment, different types of compounds of Formula 1 in the composite collector, Formula 1-b, Formula 1-a, Formula 1-c, and Formula 1-d, are used to flotate the composite lithium ore in Table 1. Figure 1 In the process flow shown, the flotation process parameters of each group of cases are the same, and the only difference is the type of compound of formula 1, so as to explore the selectivity and flotation effect of the composite collector in this case.
[0092]
[0093] In this case, the collector is composed of 68 parts of industrial oleic acid with a saponification rate of 60%, 12 parts of n-hexanol, 16 parts of kerosene, and 4 parts of the compound of formula 1, calculated by weight. After sufficient reaction, a 5% concentration composite collector solution is prepared for standby use.
[0094] The operation process is consistent with that in Example 1.
[0095] Table 4 shows the flotation effect of composite lithium ore under different types of primary alcohols.
[0096] Table 4 Flotation effect of composite lithium ore under different types of primary alcohol
[0097]
[0098]
[0099] It can be seen from Table 4 that under different types of compounds of Formula 1, the composite collector of the present invention has a good flotation effect on low-grade composite lithium ore, the Li2O grade in the obtainable lithium concentrate is about 4%, the enrichment ratio is greater than 5, and the Li2O recovery rate reaches more than 70%. It shows that the composite collector described in this case 2 can efficiently sort low-grade composite lithium ore under different types of compounds of Formula 1, and different types of compounds of Formula 1 have little effect on its collection ability and good stability. Comprehensively considering the compound of Formula 1 in the composite collector of the present invention, Formula 1-a is selected as the preferred one for subsequent experiments and tests.
[0100] Example 4
[0101] use Figure 1 The process flow shown in the figure is respectively implemented with different composite collectors 1 # ~4 # Composite lithium ore flotation was carried out. The flotation process parameters of each group of cases were the same, and the only difference was the different proportions of the composite collector components, so as to explore the selectivity and flotation effect of the composite collector in this case.
[0102] Implementation of composite collector 1 # : 56 parts of industrial oleic acid with a saponification rate of 60%, 14 parts of n-hexanol, 20 parts of kerosene, and 10 parts of formula 1-a.
[0103] Implementation of composite collector 2 # : 62 parts of industrial oleic acid with a saponification rate of 60%, 14 parts of n-hexanol, 18 parts of kerosene, and 6 parts of formula 1-a.
[0104] Implementation of composite collector 3 # : 68 parts of industrial oleic acid with a saponification rate of 60%, 12 parts of n-hexanol, 16 parts of kerosene, and 4 parts of formula 1-a, referred to as YGM-1.
[0105] Implementation of composite collector 4 # : 74 parts of industrial oleic acid with a saponification rate of 60%, 8 parts of n-hexanol, 14 parts of kerosene, and 4 parts of formula 1-a.
[0106] The operation process is consistent with that in Example 1.
[0107] Table 5 shows the flotation effect of composite lithium ore under different component ratios of composite collector.
[0108] Table 5 Flotation effect of composite lithium ore under different composition ratios of composite collector
[0109]
[0110]
[0111] It can be seen from Table 5 that under different composition ratios of the composite collector, the composite collector of the present invention has a good flotation effect on low-grade composite lithium ore. Taking comprehensive consideration, the composite collector YGM-1 of the present invention is selected as the preferred one for subsequent experiments and tests.
[0112] Example 5
[0113] use Figure 1 The process flow shown in the figure uses different activating agent water-soluble copper salt types, namely copper chloride, copper sulfate, copper nitrate and copper acetate, for composite lithium ore flotation. The composite collector uses the preferred YGM-1 in Example 4. The flotation process parameters of each group of cases are the same, and the only difference is the type of water-soluble copper salt, so as to explore the selectivity and activation effect of the water-soluble copper salt in this case.
[0114] The operation process is consistent with that in Example 1.
[0115] Table 6 shows the flotation effect of composite lithium ore under different types of activator water-soluble copper salts.
[0116] Table 6 Flotation effect of composite lithium ore under different types of activating water-soluble copper salts
[0117]
[0118]
[0119] It can be seen from Table 6 that under different types of water-soluble copper salts as activators, the Li2O grade in the lithium concentrate that can be obtained is greater than 3.9%, and the Li2O recovery rate reaches a good index of more than 70%, indicating that most water-soluble copper salts can well activate the composite lithium ore containing spodumene, lepidolite, and pyroxenite. Considering comprehensively, copper sulfate was selected as the preferred activator for subsequent experiments and tests.
[0120] Example 6
[0121] use Figure 1 The process flow shown in the figure uses different slurry pH values of 10.3, 10.5, 10.7 and 10.9 for composite lithium ore flotation. The flotation process parameters of each group of cases are the same, and the only difference is the slurry pH value. This is to explore the selectivity and flotation effect of the composite collector under different slurry pH values in this case.
[0122] The operation process is consistent with that in Example 1.
[0123] Table 7 shows the flotation effect of composite lithium ore at different pulp pH.
[0124] Table 7 Flotation effect of composite lithium ore at different pulp pH
[0125]
[0126]
[0127] It can be seen from Table 7 that the best slurry pH is 10.5. The increase or decrease of slurry pH will lead to the deterioration of the quality of the obtained lithium concentrate, indicating that the appropriate slurry pH is conducive to the flotation recovery of composite lithium ore. Considering comprehensively, the slurry pH of 10.5 was selected as the optimal one for subsequent experiments and tests.
[0128] Example 7
[0129] use Figure 1 The process flow shown in the figure carries out composite lithium ore flotation at different slurry temperatures of 10°C, 20°C, 30°C and 40°C. The flotation process parameters of each group of cases are the same, and the only difference is the slurry temperature, so as to explore the selectivity and flotation effect of the composite collector YGM-1 at different slurry temperatures in this case.
[0130] The operation process is consistent with that in Example 1.
[0131] Table 8 shows the flotation effect of composite lithium ore at different slurry temperatures.
[0132] Table 8 Flotation effect of composite lithium ore at different slurry temperatures
[0133]
[0134]
[0135] It can be seen from Table 8 that when the pulp temperature is 10°C, the Li2O grade in the lithium concentrate obtained is 3.86%, the enrichment ratio is 5.22, and the Li2O recovery rate can reach 70.06%. Compared with the pulp temperature of 20°C, the flotation index is only slightly reduced, indicating that the new composite collector provided by the present invention has a certain low temperature resistance. If the pulp temperature is further increased, the flotation index will increase, but the corresponding production cost will increase. Considering comprehensively, the pulp temperature of 20°C is selected as the preferred one for subsequent experiments and tests.
[0136] Comparative Example 1
[0137] Process flow and Example 4 # The same, the only difference is that the composite collector is changed:
[0138] The collector of this comparative example is a conventional lithium ore agent: calculated by weight, it is a mixture of 70 parts of oxidized paraffin soap and 30 parts of cyclopentane acid soap, which is completely dissolved at 200°C on a heating plate and then cooled to form a 5% concentration composite collector solution for standby use, referred to as PNS.
[0139] The flotation process of the composite lithium ore is the same as that in the embodiment, but the activator and collector are different, and the changes are as follows:
[0140] Primary roughing operation: activator calcium chloride 200g / t, PNS 800g / t;
[0141] One-time sweeping operation: activator calcium chloride 100g / t, PNS 400g / t;
[0142] The test results are shown in Table 9.
[0143] Comparative Example 2
[0144] Process flow and Example 4 # The same, the only difference is that the composite collector is changed, and a single industrial oleic acid with a saponification rate of 60%, referred to as SOA, is used to replace the composite collector (the total amount of the replaced collector is the same as the composite collector in Example 4). The flotation process of the composite lithium ore is the same as that in the embodiment, but the changed reagents in the flotation operation are:
[0145] Primary roughing operation: SOA 800g / t;
[0146] One-time sweeping operation: SOA 400g / t;
[0147] The test results are shown in Table 9.
[0148] Comparative Example 3
[0149] Process flow and Example 4 # The same, magnetic separation and desludging operating conditions remain unchanged, but the composite lithium ore collector is two components. Compared with YGM-1, kerosene and formula 1-a are removed: in terms of mass proportion, it is a mixture of 84 parts of industrial oleic acid with a saponification rate of 60% and 16 parts of n-hexanol. After sufficient reaction, it is configured into a 5% concentration of composite collector solution for stand-alone use, referred to as YGM-2.
[0150] The flotation process of the composite lithium ore is the same as that of Example 1, but the changed reagents in the flotation operation are:
[0151] Primary roughing operation: YGM-2 800g / t;
[0152] One-time sweeping operation: YGM-2 400g / t;
[0153] The test results are shown in Table 9.
[0154] Comparative Example 4
[0155] Process flow and Example 4 # The same, magnetic separation and desludging operating conditions remain unchanged, but the composite lithium ore collector has two components. Compared with YGM-1, n-hexanol and formula 1-a are removed: in terms of mass proportion, it is a mixture of 84 parts of industrial oleic acid with a saponification rate of 60% and 16 parts of kerosene. After sufficient reaction, it is configured into a 5% concentration composite collector solution for stand-by use, referred to as YGM-3.
[0156] The flotation process of the composite lithium ore is the same as that in the embodiment, but the changed reagents in the flotation operation are:
[0157] Primary roughing operation: YGM-3 800g / t;
[0158] One-time sweeping operation: YGM-3 400g / t;
[0159] The test results are shown in Table 9.
[0160] Comparative Example 5
[0161] Process flow and Example 4 # The same, magnetic separation and desludging conditions remain unchanged, but the composite lithium ore collector has two components. Compared with YGM-1, n-hexanol and kerosene are removed: according to the mass ratio, it is mixed with 84 parts of industrial oleic acid with a saponification rate of 60% and 16 parts of formula 1-a. After sufficient reaction, it is configured into a 5% concentration composite collector solution for standby use, referred to as YGM-4.
[0162] The flotation process of the composite lithium ore is the same as that in the embodiment, but the changed reagents in the flotation operation are:
[0163] Primary roughing operation: YGM-4 800g / t;
[0164] One-time sweeping operation: YGM-4 400g / t;
[0165] The test results are shown in Table 9.
[0166] Comparative Example 6
[0167] Process flow and Example 4 # The same, magnetic separation and desludging operating conditions remain unchanged, but the composite lithium ore collector has three components. Compared with YGM-1, formula 1-a is removed: in terms of mass proportion, it is a mixture of 68 parts of industrial oleic acid with a saponification rate of 60%, 14 parts of n-hexanol, and 18 parts of kerosene. After sufficient reaction, it is configured into a 5% concentration composite collector solution for stand-alone use, referred to as YGM-5.
[0168] The flotation process of the composite lithium ore is the same as that in the embodiment, but the changed reagents in the flotation operation are:
[0169] Primary roughing operation: YGM-5 800g / t;
[0170] One-time sweeping operation: YGM-5 400g / t;
[0171] The test results are shown in Table 9.
[0172] Comparative Example 7
[0173] Process flow and Example 4 # The same, magnetic separation and desludging conditions remain unchanged, but the composite lithium ore collector has three components, compared with YGM-1, kerosene is removed: according to the mass ratio, it is mixed with 76 parts of industrial oleic acid with a saponification rate of 60%, 16 parts of n-hexanol, and 8 parts of formula 1-a. After sufficient reaction, it is configured into a 5% concentration composite collector solution for standby use, referred to as YGM-6. (The total amount of the replaced collector is the same as the composite collector of Example 4)
[0174] The flotation process of the composite lithium ore is the same as that in the embodiment, but the changed reagents in the flotation operation are:
[0175] Primary roughing operation: YGM-6 800g / t;
[0176] One-time sweeping operation: YGM-6 400g / t;
[0177] The test results are shown in Table 9.
[0178] Comparative Example 8
[0179] Process flow and Example 4 #The same, magnetic separation and desludging conditions remain unchanged, but the composite lithium ore collector has three components. Compared with YGM-1, n-hexanol is removed: according to the mass proportion, it is mixed with 76 parts of industrial oleic acid with a saponification rate of 60%, 16 parts of kerosene, and 8 parts of formula 1-a. After sufficient reaction, it is configured into a 5% concentration composite collector solution for stand-alone use, referred to as YGM-7.
[0180] The flotation process of the composite lithium ore is the same as that in the embodiment, but the changed reagents in the flotation operation are:
[0181] Primary roughing operation: YGM-7 800g / t;
[0182] One-time sweeping operation: YGM-7 400g / t;
[0183] The test results are shown in Table 9.
[0184] Comparative Example 9
[0185] Process flow and Example 4 # The same, magnetic separation and desludging conditions remain unchanged, compared with YGM-1, sodium oleate replaces the industrial oleic acid with a saponification rate of 60%: according to the mass proportion, it is mixed with 68 parts of sodium oleate, 12 parts of n-hexanol, 16 parts of kerosene, and 4 parts of formula 1-a. After sufficient reaction, it is configured into a 5% concentration of composite collector solution for stand-by use, referred to as YGM-8.
[0186] The flotation process of the composite lithium ore is the same as that in the embodiment, but the changed reagents in the flotation operation are:
[0187] Primary roughing operation: YGM-8 800g / t;
[0188] One-time sweeping operation: YGM-8 400g / t;
[0189] The test results are shown in Table 9.
[0190] Comparative Example 10
[0191] Process flow and Example 4 # The same, magnetic separation and desludging conditions remain unchanged, compared with YGM-1, the n-hexanol is replaced by liquid paraffin: according to the mass proportion, it is mixed with 68 parts of industrial oleic acid with a saponification rate of 60%, 12 parts of liquid paraffin, 16 parts of kerosene, and 4 parts of formula 1-a. After sufficient reaction, it is configured into a 5% concentration composite collector solution for stand-by use, referred to as YGM-9.
[0192] The flotation process of the composite lithium ore is the same as that in the embodiment, but the changed reagents in the flotation operation are:
[0193] Primary roughing operation: YGM-9 800g / t;
[0194] One-time sweeping operation: YGM-9 400g / t;
[0195] The test results are shown in Table 9.
[0196] Comparative Example 11
[0197] Process flow and Example 4 # The same, magnetic separation and desludging conditions remain unchanged, compared with YGM-1, kerosene is replaced by gasoline: according to the mass proportion, it is mixed with 68 parts of industrial oleic acid with a saponification rate of 60%, 12 parts of n-hexanol, 16 parts of gasoline, and 4 parts of formula 1-a. After sufficient reaction, it is configured into a 5% concentration composite collector solution for stand-by use, referred to as YGM-10.
[0198] The flotation process of the composite lithium ore is the same as that in the embodiment, but the changed reagents in the flotation operation are:
[0199] Primary roughing operation: YGM-10 800g / t;
[0200] One-time sweeping operation: YGM-10 400g / t;
[0201] The test results are shown in Table 9.
[0202] Comparative Example 12
[0203] Process flow and Example 4 # The same, magnetic separation and desludging operating conditions remain unchanged, compared with YGM-1, methyl silicone oil replaces the formula 1-a: in terms of mass proportion, it is a mixture of 68 parts of industrial oleic acid with a saponification rate of 60%, 12 parts of n-hexanol, 16 parts of kerosene, and 4 parts of methyl silicone oil. After sufficient reaction, it is configured into a 5% concentration of composite collector solution for stand-alone use, referred to as YGM-11.
[0204] The flotation process of the composite lithium ore is the same as that in the embodiment, but the changed reagents in the flotation operation are:
[0205] Primary roughing operation: YGM-11 800g / t;
[0206] One-time sweeping operation: YGM-11 400g / t;
[0207] The test results are shown in Table 9.
[0208] Comparative Example 13
[0209] Process flow and Example 4 # The composite lithium ore collector is YGM-1, and only calcium chloride is used to replace the copper salt in one roughing operation and one scavenging operation. Other operations and parameters are the same as those in Example 4:
[0210] Primary roughing operation: calcium chloride 200g / t, YGM-1 800g / t;
[0211] One-time sweeping operation: calcium chloride 100g / t, YGM-1 400g / t;
[0212] The test results are shown in Table 9.
[0213] Comparative Example 14
[0214] Process flow and Example 4 # The composite lithium ore collector is YGM-1, and only the copper salt is replaced by ferric chloride in one roughing operation and one scavenging operation. The other operations and parameters are the same as those in Example 4:
[0215] Primary roughing operation: ferric chloride 200g / t, YGM-1 800g / t;
[0216] One-time sweeping operation: ferric chloride 100g / t, YGM-1 400g / t;
[0217] The test results are shown in Table 9.
[0218] Table 9 Test results of comparative examples 1 to 14
[0219]
[0220]
[0221]
[0222] It can be seen from Table 9 that in Comparative Example 1, the conventional lithium ore composite collector PNS was used, and only the lithium concentrate Li2O grade was 3.25%, the enrichment ratio was 4.39, and the Li2O recovery rate was 48.94%, indicating that the conventional lithium ore composite collector PNS could not achieve flotation recovery of the composite lithium ore.
[0223] When the composite collector is mixed with different components, the changes are as follows:
[0224] 1. In Comparative Example 2, SOA was used alone, and the Li2O grade in the obtained lithium concentrate was 3.78%, the enrichment ratio was 5.11, and the Li2O recovery rate was 64.77%, indicating that SOA had a certain collection capacity for the composite lithium ore using copper sulfate activation, but could not achieve the lithium ore development standard of a recovery rate greater than 70%;
[0225] 2. By reducing the components in the composite collector YGM-1 (Comparative Examples 3 to 8), the obtained lithium concentrate Li2O grade is 3.68% to 3.83%, and the Li2O recovery rate is 65.02% to 68.93%, indicating that high-quality lithium concentrate products cannot be obtained by removing the components and the remaining components;
[0226] 3. By replacing the components in the combined collector YGM-1 (Comparative Examples 9 to 12), the Li2O grade of the obtained lithium concentrate is 3.23% to 3.79%, and the Li2O recovery rate is 55.75% to 67.61%, indicating that the indicators of the lithium concentrate have decreased by replacing the components in YGM-1;
[0227] This indicates that the specific components in the composite collector of the present invention influence each other, different collectors play different roles on the mineral surface, and synergistically interact with each other to make the adsorption layer of the agent on the surface of the useful mineral more dense, thereby effectively improving the flotation effect.
[0228] When the type of activator is changed (Example 5 and Comparative Examples 13 and 14), the water-soluble copper salt copper is significantly better than the conventional activators calcium chloride and ferric chloride, indicating that the water-soluble copper salt copper can better activate the composite lithium ore containing spodumene, lepidolite, and pyroxenite, while calcium chloride and ferric chloride are not suitable for the activation of such lithium ores, resulting in the Li2O grade in the obtained lithium concentrate being only about 3%, the enrichment ratio being only about 4, and the Li2O recovery rate being only about 50%.
[0229] In summary, the composite collector of the present invention can show good low temperature resistance, selectivity and collection ability under the premise of removing magnetic gangue minerals and mud minerals. YGM-1 has the best synergistic effect on ultra-low-grade spodumene, lithium mica and phosphate lithium aluminum composite lithium ore. When the slurry pH is 10.5 and the slurry temperature is 20°C, copper sulfate is used for activation. The Li2O grade in the obtained lithium concentrate is 4.06%, the concentrate enrichment ratio is 5.56, and the Li2O recovery rate is 71.64%, which realizes the efficient recovery of the composite lithium ore and reaches the lithium ore development standard of Li2O recovery rate greater than 70%, which provides a technical basis for the subsequent development and utilization of the composite lithium ore and the establishment of a concentrator.
Claims
1. A composite collector for low-grade composite lithium ore, characterized in that: It includes saponified industrial oleic acid, kerosene, C4-C9 alcohol and a compound of formula 1; wherein the weight ratio of saponified industrial oleic acid, kerosene, alcohol and the compound of formula 1 is 55-80:10-20:5-15:4-10; Formula 1 R is C4~C 20 An alkyl group or an alkoxyalkyl group, wherein n is 1 to 14; The saponified industrial oleic acid is industrial oleic acid saponified by at least one cation of sodium and / or potassium, and its saponification rate is 40-100%; The low-grade composite lithium ore is a composite lithium ore containing two or more of spodumene, lepidolite and pyroxene, wherein the Li2O grade is less than or equal to 1%.
2. The composite collector according to claim 1, characterized in that Industrial oleic acid contains 55 to 80 parts by weight of oleic acid, 15 to 35 parts by weight of linoleic acid and 5 to 15 parts by weight of linolenic acid.
3. The composite collector according to claim 1, characterized in that The saponified industrial oleic acid is obtained by saponifying industrial oleic acid and an alkaline component, and the alkaline component is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate.
4. The composite collector according to claim 3, characterized in that The weight ratio of industrial oleic acid to alkaline components is 50~65:5~10.
5. The composite collector according to claim 1, characterized in that The alcohol is a primary alcohol of C6~C8.
6. The composite collector according to claim 1, characterized in that In the compound of formula 1, R is C7~C 16 wherein n is 5 or 12.
7. Use of the composite collector according to any one of claims 1 to 6, characterized in that: It is used for the flotation of low-grade composite lithium ores.
8. The use of the composite collector as claimed in claim 7, characterized in that: The Li2O grade of low-grade composite lithium ore is less than or equal to 0.75%.
9. A lithium ore composite flotation reagent, characterized in that: The invention comprises the composite collector according to any one of claims 1 to 6 and a water-soluble copper salt.
10. The lithium ore composite flotation reagent according to claim 9, characterized in that: The water-soluble copper salt is at least one of copper sulfate, copper chloride, copper nitrate, copper acetate and copper citrate.
11. The lithium ore composite flotation reagent according to claim 9, characterized in that: A pH adjuster is also included.
12. The lithium ore composite flotation reagent according to claim 11, characterized in that: The pH adjuster is at least one of sodium carbonate, sodium hydroxide, hydrochloric acid and sulfuric acid.
13. The lithium ore composite flotation reagent according to any one of claims 9 to 12, characterized in that: In the lithium ore composite flotation reagent, each component exists independently of each other before use, or some or all of the components exist in the form of a mixture.
14. The lithium ore composite flotation reagent according to claim 13, characterized in that: In the lithium ore composite flotation reagent, the weight portion of the composite collector is 30 to 50 parts; The weight portion of the water-soluble copper salt is 5 to 15 parts; The weight portion of the pH adjuster is 45 to 65 parts.
15. A flotation method for low-grade composite lithium ore, characterized in that: The low-grade composite lithium ore is floated using a flotation agent comprising the composite collector described in any one of claims 1 to 6.
16. The flotation method according to claim 15, characterized in that: The low-grade composite lithium ore is floated using a flotation agent as described in any one of claims 9 to 14.
17. The flotation method according to claim 15, characterized in that: Low-grade composite lithium ore is first treated with demagnetization and desludging before flotation.
18. The flotation method according to claim 15, characterized in that: The flotation steps are: co-grinding the low-grade composite lithium ore and alkaline substances, followed by demagnetization and desludging to obtain ore pulp; The pH of the ore pulp is regulated, and a water-soluble copper salt and the composite collector are added to perform flotation to obtain lithium concentrate.
19. The flotation method according to any one of claims 16 to 18, characterized in that: The pH of the pulp during the flotation stage is 10-11; The dosage of composite collector is 600~1500g / t; The dosage of water-soluble copper salt is 80~400g / t.
Citation Information
Patent Citations
Method for recycling tantalum-niobium and lithium oxide concentrate from magnetic waste sand
CN108393190A
Method for improving grade of low-grade spodumene roughing concentrate
CN113058748A